Slave families and the hato economy in Puerto Rico - Stark, David M. (Univ. Press of Florida, 2015)
This book approaches Caribbean slavery by emphasizing the importance of the hato (herding) economy on Puerto Rico rather than sugar and tobacco production. The author makes use of extensive Catholic parish records